Advances in novel parentral drug delivery systems - Patel, Rakesh; Patel, Kaushal P (Asian Journal of Pharmaceutics (AJP), 2014)
The parenteral administration route is the most effective and common form of delivery for active drug substances with poor bioavailability and the drugs with a narrow therapeutic index. Drug delivery technology that can reduce the total number of injection throughout the drug therapy period will be truly advantageous not only in terms of compliance, but also to improve the quality of the therapy. Such reduction in frequency of drug dosing is achieved by the use of specific formulation technologies that guarantee the release of the active drug substance in a slow and predictable manner. The development of new injectable drug delivery system has received considerable attention over the past few years. A number of technological advances have been made in the area of parenteral drug delivery leading to the development of sophisticated systems that allow drug targeting and the sustained or controlled release of parenteral medicines.